Evaluation of The Implementation of The Cost Structural Standard Policy - Yulianto, Jauhar Rafid; Lestari, Niken Ajeng; Hartanto, Hartanto; Febrianto, Andrie Mulya (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2020)
In order to realize an effective and efficient budgeting, a Standard Cost Structure (SSB) policy was prepared, namely by applying a supporting cost percentage for non-regulatory service output of 45%. The study analyzes how SSB policy is implemented within the Ministry of Finance, identifies the problems that occur, and provide solutions for each of these problems. The results of the study show that there is no satker in the Ministry of Finance that uses an exact amount of 45% for supporting costs in the output of its non-regulatory services. The study identifies two underlying problems. First, according to the respondents, the concept of main and supporting cost is clear and well-defined but difficult to implement. The second problem is that the RKA-KL is yet to be able to smoothly facilitate the selection of the main and supporting costs.